The Leadership Spectrum: Exploring the Complex Dynamics between Leadership Styles and Teacher Satisfaction - Ismaeel, Ghazala; Siraj, Darakhshan; Akhtar, Samina (Annals of Human and Social Sciences, 2024)
The objective of the study was to identify the relationship between leadership and job satisfaction among teachers at colleges in District Dera Ghazi Khan, located in south Punjab, Pakistan. Utilizing a correlational research design the two instruments, the Leadership Styles Measurement Questionnaire (LSMQ) and the Job Satisfaction Scale for Teachers (JSST), were utilized to collect the data. The population of the study comprised a total of 378 teachers and 17 principals from public colleges. The study sample included 308 teachers (male 121 and female 187) and 17 principals (male 8 and female 9) selected through simple random sampling from colleges. The research revealed that principals who employed the laissez-faire type of leadership have a positive influence on teacher satisfaction with professional work. On the other hand, administrators who were autocratic or democratic negatively influenced teacher satisfaction. In addition, there was a significant difference in teacher satisfaction by gender. The study recommends that principals and administrators change their leadership approach and provide support to their teachers with some autonomy to foster job satisfaction in educational institutions.